Examining Cross-Industry Clusters among Airline and Tourism Industries - Liasidou, Sotiroula (My University, 2024)
Cross-industry clusters are essential for the economic prosperity of a region. However, studies do not address competitive clusters among the airline and tourism industries. Thus, this paper considers the case of both industries in terms of the clusters and synergies formed. This research aim is to provide an understanding of both industries’ protagonists’ involvement in contributing to insights into the establishment of synergies or clusters among the two industries. Cyprus is highly dependent on tourism and airlines because they facilitate connectivity. The research comprises semi-structured interviews with the leading players and organizations of the airline and tourism industries (government bodies, airports, airlines, tour operators and hotels). The results indicate that in a small geographical context, the notion of clusters involves a synergetic relationship among tourism stakeholders. The airlines’ role is essential and affects all stakeholders involved in tourism. Additionally, the research provides new insights into the role of Destination Management Organisations (DMOs) in providing applicable tourism policies that can positively impact effective cooperation among industry partners.
Keywords: Tourism clusters; Airline; Tourism policy; Semi-structured interviews; Cyprus